Knowledge, attitudes, and practices toward seasonal influenza vaccination among healthcare workers and pregnant women in Pakistan: A mixed methods approach - Shahira Shahid; Hajra Khwaja; Shafi Kalhoro; Junaid Mehmood; Muhammad Farrukh Qazi; Abdinasir Abubakar; Shaza Mohamed; Wasiq Khan; Fyezah Jehan; Muhammad Imran Nisar (Taylor & Francis Group, 2023)
Vaccine hesitancy is a significant public health issue globally. We aim to document the barriers toward seasonal influenza vaccine uptake among healthcare workers (HCWs) and pregnant women (PW) in Pakistan. We performed a concurrent mixed methods study in four cities (Karachi, Islamabad, Quetta, and Peshawar) across Pakistan from September to December 2021. The quantitative component consisted of independent cross-sectional surveys for PW and HCWs, and the qualitative component comprised of in-depth interviews (IDIs) and focus group discussions (FGDs) among HCWs. Simple linear regression was used to determine the association of sociodemographic variables with knowledge, attitudes, and practices. Overall, 750 PW and 420 HCWs were enrolled. Among the PW, 44% were willing to receive the vaccine if available free of cost. Only 44% of the HCWs were vaccinated; however, 86% intended to get vaccinated and were willing to recommend the vaccine to their patients. HCWs refused vaccine due to side-effects (65%), cost (57%), and allergies (36%). An education level of secondary school and above was predictive of higher attitude and knowledge scores while having received the COVID-19 vaccine was associated with higher practice scores for both PW and HCWs. Several themes emerged from the interviews: 1) HCWs' knowledge of influenza and its prevention, 2) HCWs' perception of motivators and barriers to influenza vaccine uptake and 3) HCWs' attitudes towrd vaccine promotion. We report low influenza vaccine coverage among HCWs and PW in Pakistan. Educational campaigns addressing misconceptions, and improving affordability and accessibility through government interventions, can improve vaccine uptake.